2018
DOI: 10.1080/19942060.2018.1520741
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulations of the aerodynamic response of circular segments with different corner angles by means of 2D URANS. Impact of turbulence modeling approaches

Abstract: This paper presents the results of numerical and experimental investigations on the force coefficients and Strouhal numbers of circular segments considering different corner angles or chord to sagitta ratios. The research is motivated because these geometries are becoming increasingly popular in several engineering disciplines. The so-called D-section (semi-circular cylinder with a corner angle of 90 •) has been experimentally studied in the past, since it is a galloping prone geometry. However, there is a lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 105 publications
(135 reference statements)
0
6
0
Order By: Relevance
“…Many researchers have studied turbulence and discovered the law of turbulence, which is the variation of energy fluctuation with time-scale or wave number (Chen, Chen, Eyink, & Sreenivasan, 2003;Falkovich & Ryzhenkova, 1992;Frisch, 1995;Liang, Wu, & Zhong, 2017;Young & Read, 2017). So, the other two important variables for the turbulent phase transition are the energy spectrum (E k ) and time index factor (g) (Frisch, 1995;Layek & Sunita, 2018;Montoya, Nieto, Alvarez, Hernandez, & Jurado, 2018;Romero-Gomez, Harding, & Richmond, 2017).…”
Section: Quantitative Catastrophe Methods Analysis Of Turbulence Phase-transition Processmentioning
confidence: 99%
“…Many researchers have studied turbulence and discovered the law of turbulence, which is the variation of energy fluctuation with time-scale or wave number (Chen, Chen, Eyink, & Sreenivasan, 2003;Falkovich & Ryzhenkova, 1992;Frisch, 1995;Liang, Wu, & Zhong, 2017;Young & Read, 2017). So, the other two important variables for the turbulent phase transition are the energy spectrum (E k ) and time index factor (g) (Frisch, 1995;Layek & Sunita, 2018;Montoya, Nieto, Alvarez, Hernandez, & Jurado, 2018;Romero-Gomez, Harding, & Richmond, 2017).…”
Section: Quantitative Catastrophe Methods Analysis Of Turbulence Phase-transition Processmentioning
confidence: 99%
“…Den Hartog [13] was the first to study this geometry's galloping instabilities, while Novak and Tanaka [14] reported the effects on the galloping instability and force coefficients caused by smooth and turbulent flows. Cid Montoya et al [15] addressed the semi-circular cylinder force coefficients and Strouhal number depending on the Reynolds number and the angle of attack. However, no significant study has been published regarding piezoelectric energy harvesting from aeroelastic phenomena present in the semi-circular cylinder at the angles of attack reported herein.…”
Section: Energy Harvesting Systemsmentioning
confidence: 99%
“…where f n is a natural frequency of the dynamical system, D is the reference length and St is the Strouhal number that can be measured through aerodynamic wind tunnel tests for each bluff body. In this work, values of the critical Strouhal number for the semi-circular cross-section were taken from Montoya et al [15], and the natural frequencies of the body were measured in the wind tunnel facility to identify the critical VIV flow speed for the sectional models and prototype.…”
Section: Vortex-induced Vibrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The objective of this work is to assess the feasibility of a semi-circular cylinder, whose aerodynamic characteristics were previously studied based on experimental tests and numerical simulations [2], to generate large wind-induced oscillations in a classical harvester configuration based on a cantilever beam with the bluff body attached to its tip and a sheet of piezoelectric material bounded close to the fixed end. Other alternative geometries have been studied as tip bluff bodies [3], [4], also considering modifications in the reference shape.…”
Section: Introductionmentioning
confidence: 99%